Thermo-mechanical processing of metallic materials (Pergamon materials series., 2007)
Modern metallic materials are used extensively in a wide variety of applications, some of which are quite obvious (vehicles, cables, buildings and packaging) and others perhaps less so as in the critical structures of planes, skyscrapers, micro-electronic devises, nuclear and other energy plants. Many of the alloys used for these applications have undergone major transformations over the last 20 years. These transformations have been implemented to improve the material performances at minimum cost to the user. In many cases, if not most, they have resulted from advances in Thermo-Mechanical Processing the set of operations by which basic materials are transformed into high quality components. Divided into three sections, the first section covers the microstructural science base of the subject, including the microstructure determined mechanical properties of metals. The second section deals with the current mechanical technology of plastic forming of metals. The concluding section illustrates the interaction of the first two disciplines in a series of case studies of successful current TMP processing and also looks ahead to possible new developments in the field. This book aims to fill this gap between two scientific approaches and illustrate also their successful linkage by the use of suitable modern case studies. * Covers both physical metallurgy and metals processing * Links basic science to real everyday applications * Written by four internationally-known experts in the field.